Mutual Coupling Reduction between Patch Antennas Using Meander Line. (4th July 2018) - Li, Qian; Ding, Chong; Yang, Ruichao; Tan, Mingtao; Wu, Gangxiong; Lei, Xia; Jiang, Xuebing; Fang, Shuanzhu; Huang, Minzhi; Gong, Yubin; Wei, Yanyu
Abstract : Meander lines (MLs) in two configurations are presented to reduce the mutual coupling (MC) between two microstrip patch antenna elements. Inserting a slot in the ground plane between the antenna elements is a simple method to reduce the MC, while adding the MLs in the slot of the ground can further reduce the MC. In the first configuration, one ML is inserted in the slot of the ground and a maximum MC reduction of 39 dB throughout the −10 dB bandwidth is achieved. What's more, the radiation patterns are not changed compared with the dual-element microstrip antenna array with a slotted ground. For the second configuration, two MLs are added in the slot of the ground. It is found that a maximum isolation of 53 dB can be obtained. However, the radiation patterns are slightly changed compared with the dual-element microstrip antenna array with a slot in the ground. Meanwhile, the measured peak gain and efficiency of the dual-element microstrip antenna array in the two configurations are given. Along with this paper, several prototypes have been fabricated and measured. The simulated results are in good accordance with the measurements, which are presented to verify that MC reduction can be achieved between microstrip antenna elements by adding the MLs in the slotted ground.